Quetiapine and Clarithromycin–Induced Neuroleptic Malignant Syndrome. Issue 1 (January 2015) - Christodoulou, Christos; Margaritis, Dimitris; Makris, Gerasimos; Kavatha, Dimitra; Efstathiou, Vasiliki; Papageorgiou, Charalabos; Douzenis, Athanasios
<x xml:space="preserve">Abstract</x> Abstract We report a case of neuroleptic malignant syndrome possibly caused by the combined administration of quetiapine and clarithromycin in a 75-year-old male patient. He was receiving quetiapine regularly. Two days before his admission to the hospital, he had been feverish and started receiving clarithromycin without consulting a doctor. Clarithromycin administration was interrupted 3 days after his admission because it was ineffective and because his clinical state was deteriorating. The patient presented altered level of consciousness and excessive muscular rigidity on his limbs, while he remained feverish (38.7 °C). Laboratory abnormalities included elevated serum creatine phosphokinase level (5.387 U/L), leukocytosis, and low serum iron. The patient was diagnosed with neuroleptic malignant syndrome, and quetiapine was immediately discontinued. After the following days, his muscle rigidity and mental status ameliorated, his fever withdrew, and his laboratory findings improved. The various features of the case are discussed in view of the fact that the concomitant administration of cytochrome 3A4 inhibitors, such as clarithromycin, is suggested to cause an increase of plasma concentrations of quetiapine. Thus, physicians should have a high index of suspicion of the interactions of commonly administered medications.